Pengaruh pengulangan pengapuran dengan kapur tohor (CaO) terhadap kualitas fisik kulit pari tersamak - Aidil Rahmat; Latif Sahubawa; Iwan Yusuf (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2008)
The objective of this research was to know the influence of reliming on physical properties of tanned stingray skin. The research used randomized completely block design with three treatments. The treatment consisted of: liming once (PI), liming twice (P2), and liming three times (P3). Quality parameters analyzed were tensile strength (%), elongation at break (kg/cm2), and skin suffocation organoleptically. The data were analyzed by analysis of variance methods and subsequently by Least Significant Differences Test, α. 0,05. The results showed that elongation at break tanned stingray skin of P1, P2, and P3 respectively were 26.5, 30.0, and 32.0%. Result analysis of tensile strength tanned stingray skin of treatment P1, P2, and P3 respectively were 238,04 ; 259,53 : and 270,89 kg/cm2. The result analysis of suffocation tanned stingray skin of treatment P1, P2, and P3 respectively were 1,78 ; 2,13 and 2,45. The P3 treatment effected the tanned stingray skin on the tensile strength, elongation at break and skin suffocation, and meet the requirement of SNI 06-6121-1999, about the quality criterion for stingray skin leather product.Key words : tanned stingray skin, reliming, CaO lime, physical properties ABSTRAK Tujuan penelitian adalah mengkaji pengaruh variasi pengulangan pengapuran terhadap kualitas fisik kulit ikan pari tersamak. Rancangan percobaan yang dipakai adalah Rancangan Acak Lengkap Blok (RALB) dengan pengulangan pengapuran berturut-turut 1 kali (P1), 2 kali (P2), dan 3 kali (P3). Parameter mutu kulit yang diamati yaitu kemuluran, kekuatan tarik serta kelemasan kulit secara inderawi. Data hasil pengamatan dianalisis secara statistic keragaman, dan dilanjutkan dengan uji Beda Nyata Terkecil (BNT) pada tingkat kepercayaan 95% (α.0,05). Hasil percobaan menunjukan bahwa kemuluran kulit pari tersamak dari pengulangan pengapuran P1,P2, dan P3 berturut-turut 238,04 ; 259,53 & 270,89 kg/cm2. Kelemasan kulit pari tersamak dari pengapuran 3 kali (P3), mampu menghasilkan kualitas kulit ikan pari tersamak dengan sifat kekuatan tarik, kemuluran, & kelemasan yang terbaik, dan memenuhi syarat mutu yabg ditetapkan dalam SNI 06-6121-1999 tentang persyaratan mutu kulit pari untuk produk barang kulit.Kata kunci : kulit pari tersamak, pengapuran, kapur CaO, sifat fisik